EFEKTIVITAS TERAPI RELAKSASI OTOT TERHADAP TENSION TYPE HEADACHE: Systematic Review - Hana Nur Hanifah (2022)
Background: Headache disorder is one of the most common disorders of the nervous system and is most often found in daily practice. Approximately in one year, 90% of the world's population experience headache at least once. Tension-type headache is a painful condition in the front (frontalis) and back of the head (occipitalis) caused by persistent muscle tension in the muscles of the head and neck. Non-pharmacological management by performing muscle relaxation techniques are used in overcoming tension-type headache as an alternative or complementary therapy. This systematic literature review study aims to determine the effectiveness of muscle relaxation therapy methods for patients with tension-type headache. Methods: This study was conducted using the PRISMA-P 2020 flow chart by reviewing the literature obtained through the SCIENCE DIRECT, PubMed, Cochrane databases based on inclusion and exclusion criteria. Results: The data obtained are eight pieces of literatures that show the results that there is effectiveness of therapeutic methods against tension-type headache by providing positive impacts including pain intensity, pain frequency, pain duration, pain threshold, and quality of life. Types of muscle relaxation therapy methods in the literature are dry needling, biofeedback, stretching, acupuncture, massage, and manual therapy consisting of myofascial inhibitory techniques and articulatory manipulations. Conclusion: Muscle relaxation therapy method is effective in tension-type headache.